KEMAMPUAN TANAMAN AIR PURUN (Lepiromia micronata) DALAM MENYERAP LOGAM BERAT (Pb, Cu dan Zn) DI BEKAS PENAMBANGAN TIMAH - UMROH UMROH (Akuatik: Jurnal Sumberdaya Perairan, 2011)
Bangka Belitung Islands Province is one of the tin-producing areas, where tin mining activities are always leaving degradation the soil, vegetation and wastes that are toxic, especially some heavy metals such as Pb, Cu and Zn in soil and in the former tin mine excavation called kolong. Greatly affect the quality of waste water and cause pollution, it is feared could extend to land and waters around so that endanger residents. Based on the results of research conducted on the measurement of three former tin mining at different age levels (0, ±8, and> 15 years), it can be concluded that the older age, so the content of heavy metals (Cu, Pb and Zn) is decrease. This is caused by several factors, such as the ability of aquatic plants (Lepiromia micronata) which accumulate heavy metals and other factors such as rain water dilution and precipitation. The results showed that endemic plants can absorb heavy metals. Therefore, heavy metal reduction of tin mining in Bangka Island using phytoremediation method by aquatic plant, because it is relatively inexpensive, easy and environmentally friendly.